Exploring households' willingness to pay for improvements in water services: a case study in Terengganu, Malaysia (a pilot study) - S., Kuna; Kamaludin, Mahirah; Abd. Aziz, Azlina; Anang, Zuraini; Radam, Alias (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2015)
Malaysia has abundant of water resources which consist of surface and groundwater. As human population increases gradually, the demand for water resources also increases. Syarikat Air Terengganu Bhd. (SATU) faces several problems related to water services in Terengganu such as, low water pressure, overflow tank, leaking pipeline, breaking and stealing of pipelines and many more. The main objective of this study is to determine consumer’s willingness to pay (WTP) for an appropriate water pricing and improvement in domestic water service in the state. This study employs a pilot test study which is applying Contingent Valuation Method (CVM) with 60 respondents (households) in all districts of Terengganu. Several factors such as, resident’s income, water price, level of education, size of house, race and others were taken into consideration during surveys in order to determine the willingness to pay (WTP). The customers’ WTP for improved water quality and efficient water services for customers in Terengganu will be estimated. The estimated mean WTP for improved domestic water services is RM0.686 applies on first 30m3. The price is an increase about RM0.186 from the current price which is RM0.50 applies on first 30m3. Based on these findings, several policies have been recommended for serious water problems faced in Terengganu.